A magic bullet for sepsis – a needle in a haystack or barking up the wrong tree?. Issue 11 (November 2015) - Headley, Pádraig; Russell, Conn
Abstract: Severe sepsis causes significant morbidity and mortality and constitutes a considerable burden on the National Health Service. Our understanding of the pathophysiology, molecular processes and genomics is gradually improving. There is increasing attention being paid on trying to find a novel targeted treatment for sepsis. However, no agent to date has weathered clinical trials and analyses. One that came close was activated protein C, but it has now been removed from the market due to lack of clinical efficacy. The purpose of this article is to explore current theories underpinning the scientific basis and pathophysiology of sepsis, and to link it to the search for targeted therapies.